2019
DOI: 10.4314/bajopas.v11i1.71s
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ticks on dogs in Jos, Plateau state, Nigeria

Abstract: INTRODUCTION Dogs are trained and used to unravel criminal intelligence by law enforcement agents, others keep them as pets and to others they serve as meet. In some communities they are used for hunting and sports (Arong et Hoogstraal, 1956). Ticks are vectors of important haemoparasitic diseases of dogs leading to weakness, depression, irritation and splenomegaly, surpassing all other arthropods, apart from mosquitoes, as disease agents (Hoogstraal, et al, 1964). These disease such as Haemobatonella canis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
3
0
0
Order By: Relevance
“…In line with our findings, the brown dog tick, R. sanguineus , has been reported to be the most prevalent tick species of dogs in Nigeria (Adetayo et al., 2021 ; Akande et al., 2018 ; Kamani et al., 2018; Shitta et al., 2018 ) and other parts of the world including Algeria (Kebbi et al., 2019 ) Egypt (Abdullah et al., 2016 ), Great Britain (Smith et al., 2011 ), Italy (Maurelli et al., 2018 ), Indonesia (Hadi et al., 2016 ) and China (Zhang et al., 2017 ). The 61.8% prevalence of R. sanguineus we observed in this study is within the prevalence documented by previous researchers on the abundance of R. sanguineus within and outside of Nigeria (Abdullah et al., 2016 ; Akande et al., 2018 ; Maurelli et al., 2018 ; Shitta et al., 2018 ). Amblyomma variegatum and Haemaphysalis leachi have been reported to infest dogs in Nigeria ( Akande et al., 2018 ; Konto et al., 2014; Shitta et al., 2018 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our findings, the brown dog tick, R. sanguineus , has been reported to be the most prevalent tick species of dogs in Nigeria (Adetayo et al., 2021 ; Akande et al., 2018 ; Kamani et al., 2018; Shitta et al., 2018 ) and other parts of the world including Algeria (Kebbi et al., 2019 ) Egypt (Abdullah et al., 2016 ), Great Britain (Smith et al., 2011 ), Italy (Maurelli et al., 2018 ), Indonesia (Hadi et al., 2016 ) and China (Zhang et al., 2017 ). The 61.8% prevalence of R. sanguineus we observed in this study is within the prevalence documented by previous researchers on the abundance of R. sanguineus within and outside of Nigeria (Abdullah et al., 2016 ; Akande et al., 2018 ; Maurelli et al., 2018 ; Shitta et al., 2018 ). Amblyomma variegatum and Haemaphysalis leachi have been reported to infest dogs in Nigeria ( Akande et al., 2018 ; Konto et al., 2014; Shitta et al., 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…The 61.8% prevalence of R. sanguineus we observed in this study is within the prevalence documented by previous researchers on the abundance of R. sanguineus within and outside of Nigeria (Abdullah et al., 2016 ; Akande et al., 2018 ; Maurelli et al., 2018 ; Shitta et al., 2018 ). Amblyomma variegatum and Haemaphysalis leachi have been reported to infest dogs in Nigeria ( Akande et al., 2018 ; Konto et al., 2014; Shitta et al., 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…This study revealed that there is no significant difference in the sex-wise prevalence of babesiosis, but female dogs have a higher prevalence than male ones. The findings resemble those of studies conducted by Shitta et al (2012) and Phuyal et al (2017), who found higher prevalence of Babesia spp. in females than in males.…”
Section: Discussionsupporting
confidence: 87%